Comparison of the postoperative analgesic efficacy of intravenous patient-controlled analgesia with tramadol to intravenous patient-controlled analgesia with opioids - Murphy, MD, Jamie D.; Yan, MD, Dawn; Hanna, MD, Marie N.; Bravos, MD, E. David; Isaac, MD, PhD, Gillian R.; Eng, MD, Calvin A.; Wu, MD, Christopher L. (Journal of Opioid Management, 2018)
Background: Intravenous patient-controlled analgesia (IV PCA) with tramadol is an accepted method to deliver postoperative analgesia outside North America; however, the analgesic efficacy of this analgesic agent when compared with IV PCA with opioids is uncertain. As such, the authors undertook a systematic review to compare the analgesic efficacy of IV PCA tramadol with that of IV PCA with opioids. Methods: The authors used the National Library of Medicine’s Medline database to search for terms related to tramadol and patient-controlled analgesia. Inclusion criteria were randomized controlled trials (RCTs) comparing IV PCA tramadol with IV PCA opioid and RCTs published in the English language. Relevant data were abstracted from accepted studies. Meta-analysis was performed using RevMan 4.2.10 (The Cochrane Collaboration, 2004). A random effects model was used. Results: A total of 190 abstracts were obtained from the above search, and a total of 12 RCTs met the above inclusion criteria. There was no difference in weighted visual analog scale pain scores between IV PCA tramadol versus IV PCA opioid at 48 hours postoperatively or risk of sedation or fatigue. IV PCA tramadol was associated with a higher odds of postoperative nausea and vomiting [odds ratio (OR) = 1.52, 95% confidence interval (CI) = 1.07-2.14) but a lower odds of pruritus (OR = 0.43, 95% CI = 0.19-0.98). Discussion: IV PCA tramadol appears to produce similar pain scores when compared with that from IV PCA opioids; however, the side effect profile is different between the two groups. Because of the relatively small sample size, no determination of the relative “safety” (eg, respiratory depression) of one regimen over the other can be made, and larger RCTs would be needed for such a determination.